The Influence of TikTok’s For You Page And Lifestyle on Impulsive Buying Decisions of Clothing Products Among Generation Z (Digital Business Students at Universitas Negeri Medan 2021–2022) - Emya Malum Karina Tumangger; Salman Munthe (Economic: Journal Economic and Business, 2025)
This study aims to analyze the influence of TikTok's For You Page (FYP) and lifestyle on impulsive clothing purchase decisions among students of the Digital Business Study Program at Medan State University, class of 2021–2022. This research employs a quantitative approach with an associative descriptive method. Data were collected through questionnaires distributed to 110 respondents using purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS. The findings reveal that both TikTok's For You Page and lifestyle have a positive and significant effect, either partially or simultaneously, on impulsive purchase decisions. These results highlight the important role of TikTok content displayed on the FYP and students' lifestyle patterns in encouraging spontaneous buying behavior of clothing products.